Upaya Komunikasi Bhabinkamtibmas Kelurahan Limau Manis Kota Padang Dalam Pembinaan Peraturan Lalu Lintas Di Sma Negeri 15 Padang - Rayskia, Muhammad Iqbal; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This study aims to explore the communication efforts carried out by Bhabinkamtibmas in Limau Manis Sub-district, Padang City, in fostering traffic regulations at 15 Senior High School State of Padang City. This study uses a qualitative method to understand the approaches used by Bhabinkamtibmas in fostering traffic regulations among students. The Theory that will be used is the Communication Campaign Components Model. The research findings show that Bhabinkamtibmas in Limau Manis implements three efforts in fostering traffic regulations, namely preventive, persuasive, and repressive. During the fostering activities at 15 Senior High School State of Padang City, Bhabinkamtibmas in Limau Manis delivers important messages to students, such as the importance of wearing helmets, using rearview mirrors, having non-noisy exhaust pipes, and not riding with more than two people. The fostering activities conducted by Bhabinkamtibmas have proven to be quite effective with changes in students' behavior and good cooperation between the school and Bhabinkamtibmas. (Times New Roman 9, single spaced and italicized), up to 1 page.